Analisis Pemahaman dan Kesulitan Belajar Siswa Materi Bioteknologi Berdasarkan Indikator Kelas IX SMP Se-Kota Padang Sidempuan - Zetkas, Eryati; Harahap, Fauziyah; Edi, Syahmi (Jurnal Pendidikan Biologi, 2016)
This study aims to determine; (1) The number of students who completed the material Biotechnology; (2) Analyze the indicator most elusive . This research is descriptive qualitative, the population of the research students of SMP Negeri 5 in the city Padangsidimpuan, representing 11 SMP is in the City Padangsidimpuan. Namely SMP Negeri 2 Padangsidimpuan, SMP Negeri 4 Padangsidimpuan, SMP Negeri 8 Padangsidimpuan, SMP Negeri 9 Padangsidimpuan, SMP Negeri 10 Padangsidimpuan. Based on the results of tests mastery of biotechnology research shows that as many as 151 students who completed (45.62%) of the total 331 students and 180 students were not completed (54.38%). Based on the sub material having difficulty in tissue culture material (43.73%), media hydroponics and aeroponics (39.15%), recombination (32.05%), food biotechnology products (27.04%), and the impact of biotechnology by (23.09%). Meanwhile, based on indicators that have trouble distinguishing conventional food biotechnology products and modern (18.91%), identifying the benefits of biotechnology (30.25%), giving a few examples of the manufacture of food and beverages with the use of conventional biotechnology (30.49%), making simple food biotechnology products that can be used in everyday life (29.16%), sort the steps of making a tissue culture (13.92%), identify the process and the advantages and disadvantages of undertaking a tissue culture (51.67%), identified process and the advantages and disadvantages do hydroponics (44.27%), describe how to grow crops with aeroponic media (35.31%), identifying the gene recombination products with new properties that we want (32.03%), and identifies the impact of biotechnology (22.03%).